The study of the action of substances contained in the root of Paeonia anomala l. in relation to their use in traditional medicine - Tudev, Ariunjargal; Luvsandorj, Naranzaya; Lkhamsuren, Ulambayar; Erdenechimeg, Selenge; Sharavyn, Bold (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
The basic development of the pharmacology and pharmacy of Traditional Mongolian medicine in the twenty-first century is to study and explore the main content of ancient medical books and scriptures written by doctors of previous generations. It is important to determine and study in detail the action of the main chemical and secondary components contained in Paeonia anomala L. against the disease. Therefore, it has become a challenging issue to determine the action of the main chemical and secondary ingredients contained in the Paeonia anomala L. on the disease and to study it in detail.